Fibromyalgia patients' quality of life and pain intensity variation - Martinez,José Eduardo (2008)
INTRODUCTION: One of the most reported issues on the Fibromyalgia syndrome is the pain intensity variation and its impact on patients' life quality. OBJECTIVES: 1) to establish the correlation among pain, anxiety and depression intensity perception; 2) to determine whether there is a correlation between pain intensity variation and the impact of fibromyalgia on patients' quality of life. MATERIAL AND METHODS: A study was carried out with 21 patients, who received a diary to register their perceptions on pain, anxiety and depression intensity. The patients have made this procedure three times a day, for a fifteen-day period. The impact on life quality was measured by the the Fibromyalgia Impact Questionaire (FIQ). RESULTS: It was observed a significant variation on pain intensity during the day periods. There was not a significant variation for anxiety and depression through the day periods. It was not observed any significant correlation between pain and depression or pain and anxiety intensity perception at any time of the day, during the study period. When considering the whole study period, it was observed that there was a correlation between pain and anxiety and pain and depression in the morning. CONCLUSION: It is concluded that there is a significant pain variation through the day periods and there is a correlation between pain and anxiety and pain and depression in the morning. There is a significant correlation of life quality with pain in the morning, anxiety in the afternoon and evening; and depression in all periods of the day.